Etude des propriétés mécaniques des fibres naturelles et de leur exploitation dans l’industrie légère - Bouta, Soufian; Belhadi, Soufiane; Nessrat, Rabie (université d'eloued, 2023)
"The primary goal of our work is to develop and characterize an allied fiber reinforced lamellar organic composite material The mixture used in our study is a mixture obtained by mixing epoxy resin and allied fibers The manufacturing method that we relied on is contact molding at the university laboratory level. Studying some mechanical and physical properties when conducting a tensile test, through which we concluded that the material The vehicle used in the study is acceptable. " "الهدف الأساسي لعملنا هذا هو تطوير وتوصيف مادة مركبة صفائحية عضوية مقواة من ألياف الحلفاء. الخليط المستعمل في دراستنا هو عبارة عن مزيج متحصل من خلط الراتنج من نوع ايبوكسي وألياف الحلفاء. طريقة التصنيع التي اعتمدنا عليها هي القولبة بالتلامس على مستوى المخبر الجامعة. دراسة بعض الخصائص الميكانيكية والفيزيائية عند إجراء اختبار الشد التي من خلالها استنتجنا ان المادة المركبة المستعملة في دراسة مقبولة. "
مذكرات ماستر تخصص طاقوية Des thèses master énergitique
Keywords: Keywords: organic composite materials, plant fibers, mechanical properties.; الكلمات المفتاحية: المواد المركبة العضوية، الألياف النباتية، الخصائص الميكانيكية